MASYARAKAT PALEMBANG BUDAYA, AGAMA, ETNIS DAN PERUBAHAN - Darosan, Muslih; Fikri, Muhammad Sirajudin; Rusli, Ris’an; Niswah, Choirun (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Palembang, the capital city of South Sumatra Province, is known not only as a center of government and economy but also as a region rich in cultural heritage. As one of the oldest cities in Indonesia, Palembang has a long history marked by interactions among various ethnic groups, religions, and foreign cultural influences. This study aims to explore the development of culture, religion, and ethnicity in the city of Palembang. The research method used is a literature review, which involves systematic steps such as identifying relevant books and articles based on the research topic, collecting information from these sources, and noting important concepts and perspectives. The collected data are then filtered and grouped according to main themes, followed by analysis and presentation in a structured narrative form. The study finds that the culture of Palembang society is characterized by a dynamic creative process. The people of Palembang have experienced intense cultural mixing and assimilation, especially through interactions with foreign cultures that arrived via trade routes and conquests. The ethnic composition in Palembang consists of various groups, predominantly Malay Palembang, Javanese, Arab descendants, and Chinese. Furthermore, religion—particularly Islam—plays a central role in the life of Palembang’s society. Since the arrival of Islam in the 7th century AD, the religion has served not only as a moral foundation but has also significantly influenced local customs and traditions. The Islamization process in Palembang demonstrates a harmonious integration between religious values and local culture, resulting in a unique synthesis manifested in various ceremonies and rituals.